Burden of Osteoporotic Fractures Using Disability-Adjusted Life Years in South Korea. (March 2020) - Bae, Green; Kim, Eugene; Kwon, Hye-Young; Ha, Yong-Chan; An, Jongryun; Park, Jeehye; Yang, Hyowon
There is an increase in the number of patients with osteoporotic fractures due to the aging population in Korea. This study investigated the burden of osteoporotic fractures including hip, spine, and wrist fractures in the Korean population by estimating disability-adjusted life years (DALYs). The DALY for a given condition in a population captures years of life lost due to premature death and years of life lived with a disability and its severity and duration. To calculate DALYs from all relevant data collected for the 3 conditions, we used a DALY calculation template provided by the World Health Organization in 2014. DALYs per 100 000 for vertebral fractures (3168) were higher than those of hip fractures (2496) in women. Wrist fractures (1038) had the least burden, and the difference between men and women was the lowest. The aging population is expected to increase the burden of osteoporosis.